Implementasi Media Digital Interactive Flat Panel (IFP) dalam Mentransformasi Pembelajaran IPS di SMP Al Anwari - Abel Azka Rohmania; Dhalia Soetopo; Tofan Priananda Adinata (PEDAGOGIC: Indonesian Journal of Science Education and Technology, 2026)
This study aims to analyze the implementation of Interactive Flat Panel (IFP) as a digital media in social studies, students' responses and active involvement, as well as supporting and inhibiting factors at SMP Al Anwari Banyuwangi. This study uses a descriptive qualitative method with a purposive sampling technique. This study involved 15 informants consisting of the principal, social studies teachers, and eighth-grade students. Primary data were collected through participant observation and in-depth interviews, then analyzed using the Miles and Huberman model. The results indicate that the utilization of IFP is realized through student-needs-based preparation and student-centered instructional implementation by integrating multimedia and educational games. Based on the Cone of Experience and Constructivism theories, this digital intervention proved to elicit a highly positive response. The IFP device successfully eliminated acute classroom boredom among passive students, while simultaneously reconstructing the habituation of less-disciplined students into a more orderly and productive conduct through tactile-kinesthetic engagement on the touchscreen. The primary supporting factors include infrastructure readiness, boarding school digital policies, and student enthusiasm; whereas the inhibiting factors comprise internet network instability, gaps in digital literacy among teachers, and the risk of visual distraction on students' focus. The school is recommended to improve internet capacity and TIK training evenly